2014
DOI: 10.1159/000358004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Speech in Noise Understanding with a Direct Acoustic Cochlear Implant in Subjects with Severe to Profound Mixed Hearing Loss

Abstract: The aim of this study was to investigate the efficacy of a direct acoustic cochlear implant (DACI) for speech understanding in noise in patients suffering from severe to profound mixed hearing loss (MHL) due to various etiologies compared to the preoperative best-aided condition. The study was performed at five tertiary referral centers in Europe (Belgium, Germany, Poland and Spain). Nineteen adult subjects with severe to profound MHL due to (advanced) otosclerosis, ear canal fibrosis, chronic otitis media, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…These factors may result in reduced functioning of the CI itself as well as an increased probability of implant revisions or reimplantation [Calmels et al, 2007]. The impact of these potentially worse results on the CI user's quality of life (QoL) has been reported [Calmels et al, 2007;Lenarz et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…These factors may result in reduced functioning of the CI itself as well as an increased probability of implant revisions or reimplantation [Calmels et al, 2007]. The impact of these potentially worse results on the CI user's quality of life (QoL) has been reported [Calmels et al, 2007;Lenarz et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Another study of the group of Hannover reported the rather long adaptation phase of 12 months in CI patients, which is the time needed for the brain to adapt to electrical stimulation [Lenarz et al, 2011]. The suggestion of a faster and less effortful rehabilitation in DACI users due to more natural acoustic sound was also reported in a previous multicenter study comparing speech performance in DACI users for different pathologies [Lenarz et al, 2014].…”
Section: Discussionmentioning
confidence: 80%
“…The DACI system provides more natural hearing in contrast with electrical stimulation, and implantation with a DACI system is reversible as the incus is preserved. Even after longer rehabilitation with a DACI system, CI surgery can still be considered in case of far advanced otosclerosis and extensive cochlear involvement [Lenarz et al, 2014]. Nevertheless, similar risks -which can occur during stapedectomy/stapedotomy or CI surgery -may result due to DACI implantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations